40 OVEREXPRESSION OF ANTIOXIDANT ENZYMES IN LUNG EPITHELIAL CELLS PREVENTS DAMAGE FROM AIRBORNE PARTICULATE MATTER-INDUCED OXIDANT INJURY. (1st March 2006) - Soberanes, S.; Panduri, V.; Wang, H.; Mutlu, G.; Budinger, G. R.; Kamp, D. W.
Abstract : Elevated levels of air pollution particles are associated with increased morbidity and mortality from acute and chronic cardiopulmonary injury. One mechanism underlying these effects involves oxidative damage to lung epithelial cells. We previously showed that Düsseldorf particulate matter (DPM) causes alveolar epithelial cell DNA damage and apoptosis by a mitochondria-regulated death pathway. In this work, we used several different types of well-characterized particulates to determine whether mitochondria-derived reactive oxygen species (ROS) are the primary cause of apoptosis. Washington particulate matter (WPM), residual oil fly ash (ROFA), and DPM each increased ROS production (ASSAY HERE) and apoptosis (DNA fragmentation) as compared to inert particulates such as desert dust (DD) and Mount St Helen volcanic dust (MSH) (Table 1 ). Notably, WPM, ROFA, and DPM did not induce ROS production or apoptosis in;gr0-A549 cells, which are incapable of mitochondrial ROS production. We also found that overexpression of MnSOD or CuZnSOD using adenoviral expression vectors blocks DPM-induced A549 cell ROS production and apoptosis as compared to null/sham adenoviral controls. We conclude that a diverse group of toxic airborne particulates, unlike inert particulates, induce mitochondria-derived ROS production and lung epithelial cell apoptosis. We propose that strategies aimed at reducing mitochondrial-derived ROS levels will protect the lung epithelium exposed to airborne particulate matter. Funded by Veterans Affairs Merit Review (D.W.K.); NIH-K08 (GSB).